Avaliação clínica e laboratorial de equinos sororreagentes para Leishmania SP. no município de Belo Horizonte, Minas Gerais, Brasil - Isabel Roussoulieres Soares (2012)
This study assessed the seroprevalence for IgG anti-Leishmania sp. in drafts horses from seven differents administrative departments of the Belo Horizonte´s county. The study was carried out with the strain MHOM/BR/75/M2904 of L. (Viannia) braziliensis as antigen, intact and inactivated at 55ºC for eight minutes for the Indirect Fluorescent Antibody (IFA) test and the promastigotes were sonicated for the Enzyme-linked Immunosorbent Assay (ELISA). The methodology for the ELISA required standardization which achieved a Kappa index of 0.89, representing reliable in housereproducibility. No significant differences (p> 0.05) in the frequency distribution of reactive samples between genders and regions were detected. The agreement between the serological techniques was poor, with Kappa 0.131. The seroprevalence by combining both techniques was 30.48%. Seroprevalence estimated by positive predictive value for the IFA technique was 47.62%, and 41.43% for ELISA. The clinical and clinical-laboratory testing of reactive and non-reactive groups were compared aiming the detection of asymptomatic, symptomatic and subclinical forms, being the horse subject to present the three forms of infection. A third phase of the study evaluated the presence of genetic material of the parasite in the peripheral blood of horses using PCR test. It was determined prevalence of 16.22% (24/148) for the genus Leishmania sp., 11.49% (17/148) for L. braziliensis, 6,08% (9/148) for L. infantum and even 4.05% (9/148) of mixed infection. There was no correlation between serological techniques and molecular technique. The results emphasizes the importance of equine leishmaniosis in Equine Internal Medicine and as possible mammalian reservoir of different Leishmania species.